Migrant entrepreneurship in Hamburg: Results from a qualitative study with Turkish entrepreneurs - Andreia Tolciu; Ann-Julia Schaland; Tanja El-Cherkeh (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
This article is an overview study on migrant entrepreneurship in Hamburg with a special focus on Turkish entrepreneurs. On the basis of 58 semistructured interviews conducted between October 2008 and January 2009, several patterns such as entrepreneurial motivation, business development and embeddednes in co-ethnic or mainstream networks are closely examined. Furthermore, this article refers to problems migrant entrepreneurs encounter in the business process and illustrates formal and informal strategies applied in solving these issues. Lastly, support structures for migrant businesses in Hamburg are discussed and evaluated.
Keywords: 330; migrant entrepreneurs; migrant entrepreneurs in knowledge-intensive service sectors; social capital; co-ethnic and mainstream embeddedness; support structures for migrant businesses in Hamburg